Brotherhood, Political Attitudes, and Cadre Formation: The Dynamics of the 13th Nahdlatul Ulama Congress in 1938 in Menes, Banten - Agung Purnama; Budi Sujati (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2026)
The 13th Nahdlatul Ulama Congress in 1938, held in Menes, Banten, was a significant milestone in NU’s history, reflecting the organization’s internal dynamics and its stance toward colonial socio-political change. This study aims to examine the historical, political, and social dimensions of the congress, particularly regarding the strengthening of ukhuwah (brotherhood), political stances toward the Volksraad, and efforts to develop youth and women’s cadres. This research uses historical methods through the stages of heuristics, source criticism, interpretation, and historiography. Primary sources were obtained from NU archives and official documents, such as the congress minutes, instructions from the Head of the Nahdlatul Ulama Council (HBNO), and contemporary newspaper publications; while secondary sources include NU history books and other academic studies. The results of the study show that the 13th NU Congress not only succeeded in consolidating the internal structure through the legalization of ANO (Ansor Nahdlatul Oelama) and the discourse on the formation of Muslimat, but also confirmed the organization’s stance on involvement in the Volksraad, rejecting direct participation but still opening up diplomatic space through non-political channels. The spirit of Islamic brotherhood, emphasized by K.H. Hasyim Asy’ari, became the foundation for the unity of the people in facing external challenges and internal differences. The congress's holding in Menes also marked NU's geographical expansion beyond East Java. Thus, this congress became a strategic reflection on the process of forming NU’s identity as a socio-religious force adaptable to the dynamics of the times.